The Curvilinear Impact of Cultural Friction on Foreign Divestment - Nguyen, Ha; Larimo, Jorma; Dow, Douglas (Springer, 2024)
International business scholars have long recognized the potential influence of cultural differences on foreign divestment; however, the empirical results are mixed. Our study helps resolve this contradiction and contribute to the existing literature in three ways. First, we advocate the use of cultural friction metric, instead of the more traditional cultural distance approach. This overcomes a key limitation in the modelling the impact of cultural differences. The friction construct metric includes an index of firm-specific factors, referred to as the degree of ‘cultural interaction’. This index moderates the impact of cultural distance, reflecting firm—level differences. We also build on calls for more Positive Organizational Scholarship by challenging the negative bias in the international business literature and propose a curvilinear effect of cultural differences on divestment probability. Lastly, we investigate a potential boundary condition—the moderating effect of entry mode on the main hypothesis. Our empirical sample include 2120 Finnish foreign subsidiaries operating in 40 countries during 1970–2010. Our analyses confirm that the cultural differences, when measured by the friction metric, appear to be a significant and superior predictor of subsidiary divestment probability, and that the relationship appears to be U-shaped. Our robustness analyses also highlight the importance of which cultural framework is applied and controlling for selection bias.
Keywords: Foreign divestment; Subsidiary performance; Cultural friction; Cultural distance; Cultural distance paradox; Entry mode; fi=Kansainvälinen liiketoiminta|en=International Business|